PREEKLAMSIA, INDEKS MASSA TUBUH, PARITAS, DAN USIA SEBAGAI FAKTOR RISIKO KEJADIAN BERAT BAYI LAHIR RENDAH DI RSUD DR. M. YUNUS BENGKULU - Shofi Nur Afifah (2020)
This study aims to analyze preeclampsia, body mass index, parity, and maternal age as risk factors for the incidence of low birth weight infants in RSUD Dr. M. Yunus Bengkulu. Researchers used a Case-Control research design. Case-Control is an analytic (survey) study. This research studies how risk factor can be studied by using a retrospective approach. Data was taken by looking at maternal medical records. Data processing was diverted by chi-square test, and Mantel-Haenszel test. Based on statistical tests, preeclampsia increases the risk of LBW events by 1.688 times, and there is no significant relationship between preeclampsia and LBW events (p value = 0.149). Low body mass index increases the risk of LBW incidence by 3.995 times, and there is a significant relationship between body mass index during pregnancy with LBW incidence (p value = 0,000). Multiparous parity increases the risk of LBW events by 1,558 times, and there is no significant relationship between parity and LBW events (p value = 0.214). Age at risk increases the risk of LBW events by 2,857 times, and there is a significant relationship between maternal age and LBW events (p value = 0.006).